Savings 2.0: Harnessing Technology For Better Financial Competence - Chairul Suhendra; Aan Kanivia; Imran Imran (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research investigates the dynamics of financial competence among customers at Graha Bank Bengkulu, focusing on the roles of technology utilization and savings behavior, mediated by financial literacy. Utilizing a quantitative research design with a sample of 100 customers selected through random sampling, the study employs Smart PLS (Partial Least Squares Structural Equation Modeling) for data analysis. The results reveal significant direct effects of both technology utilization and savings behavior on financial competence, as well as a highly significant direct effect of financial literacy on financial competence. Additionally, technology utilization demonstrates a significant indirect effect on financial competence through financial literacy, while savings behavior does not exhibit a significant indirect effect. These findings underscore the importance of leveraging technological innovations and promoting financial literacy initiatives to enhance customers' financial competence and resilience. The study provides valuable insights for Graha Bank Bengkulu to develop targeted strategies and interventions aimed at empowering customers to navigate the complexities of personal finance effectively and achieve their financial goals.